Brachytherapy utilising miniaturised X-ray tubes – clinical implementation and future applications. (January 2019) - Ramachandran, P; Wanigaratne, D; Hagekrykou, J; Roozen, K; Geso, M; Kron, T; David, S
Abstract: Electronic brachytherapy is an advanced radiation treatment technique specifically designed to deliver high doses of radiation inside or very close to the tumor-bearing tissues. Unlike the traditional radionuclide-based brachytherapy, electronic brachytherapy uses a miniaturised x-ray tube that can produce radiation when energised. Most of the electronic brachytherapy systems operate at 50 kVp, therefore posing less radiation exposure to both patients and staff when compared to the standard Cobalt-60 or Iridium-192 based brachytherapy systems. Electronic brachytherapy systems have broader applications that include the treatment of skin, brain, breast, spinal metastasis, endometrium, and cervix. The Axxent Xoft brachytherapy system is a unique system which houses a miniature X-ray tube of 2.25 mm diameter at the tip of a flexible catheter. As a mobile unit, the Xoft system requires less shielding and can be operated in remote centres with minimal radiation shielding facilities. The dose fall-off characteristics mimic those of the low energy isotopes, yet the unit still maintains the high dose rate property of an Ir-192 source. This study details the implementation and commissioning aspects of the Axxent system for intra-operative radiotherapy in Breast Cancer and future applications. Electronic brachytherapy systems have the potential to replace conventional radionuclide-based brachytherapy sources and systems.